Post-Digital Cultures of the Far Right Online Actions and Offline Consequences in Europe and the US - Fielitz, Maik; Thurston, Nick (Edition Politik, 2018)
How have digital tools and networks transformed the far rights strategies and transnational prospects? This volume presents a unique critical survey of the online and offline tactics, symbols and platforms that are strategically remixed by contemporary far-right groups in Europe and the US. It features thirteen accessible essays by an international range of expert scholars, policy advisors and activists who offer informed answers to a number of urgent practical and theoretical questions: How and why has the internet emboldened extreme nationalisms? What counter-cultural approaches should civil societies develop in response?How have digital tools and networks transformed the far rights strategies and transnational prospects? This volume presents a unique critical survey of the online and offline tactics, symbols and platforms that are strategically remixed by contemporary far-right groups in Europe and the US. It features thirteen accessible essays by an international range of expert scholars, policy advisors and activists who offer informed answers to a number of urgent practical and theoretical questions: How and why has the internet emboldened extreme nationalisms? What counter-cultural approaches should civil societies develop in response?